Characterization of briquettes developed from banana peels, pineapple peels and water hyacinth - Tadeo Mibulo; Denis Nsubuga; Isa Kabenge; Kerstin D. Wydra (Energy, Sustainability and Society, 2023)
Abstract Background Uganda’s energy relies heavily on biomass sources. This dependence on biomass for household and commercial purposes, driven largely by population increase, poses pressure on natural resources, such as forests. This study investigates the usage of some of the country’s largely produced agricultural wastes for the production of biofuels. Methods Pineapple peels (PP), banana peels (BP) and water hyacinth (WH_Eichhornia crassipes (Mart.) Solms) were used for generation of both carbonized and uncarbonized briquettes. Physical properties and calorific values for the developed briquettes were determined through thermogravimetric analysis and using a bomb calorimeter. Results Pineapple peel carbonized briquettes had the highest calorific value (25.08 MJ/kg), followed by a composite of banana peels and pineapple peels (22.77 MJ/kg). The moisture content for briquettes ranged from 3.9% to 18.65%. Uncarbonized briquettes had higher volatile matter (ranging between 62.83% and 75.1%) compared to carbonized briquettes (ranging between 22.01% and 24.74%). Uncarbonized briquettes had a shorter boiling time (ranging between 27 and 36 min for 2.5 L of water) compared to carbonized briquettes (ranging between 26 and 41 min). Bulk density was highest in uncarbonized BP briquettes (1.089 g/cm3) and compressive strength was highest with carbonized BP + PP (53.22 N/mm2). When using water hyacinth alone, the produced carbonized briquettes show low calorific values (16.22 MJ/kg). However, the calorific values increased when they were mixed with banana (20.79 MJ/kg) or pineapple peels (20.55 MJ/kg). Conclusions The findings revealed that agricultural wastes could be used to augment the energy sources pool to protect the environment and create social stability in the community.